2018
DOI: 10.1037/pag0000213
|View full text |Cite
|
Sign up to set email alerts
|

Using attribute amnesia to test the limits of hyper-binding and associative deficits in working memory.

Abstract: Previous work has shown mixed evidence regarding age-related deficits for binding in working memory. The current study used the newly developed attribute amnesia effect (H. Chen & Wyble, 2015a) to test the associative-deficit hypothesis during working memory and to probe whether hyper-binding extends to include binding of de-selected information. In studies of attribute amnesia, participants use target attributes (e.g., identity, color) to demonstrate near ceiling levels of reporting of a second target attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…On the other hand, three other articles that looked at hyperbinding provide mixed and somewhat qualified support for it. First, the article by McCormick-Huhn, Chen, Wyble, and Dennis (2018) looked at binding in working memory using attribute amnesia to test the limits of both the hyperbinding suggestions and those of the ADH. Their results did not support the hyperbinding position at least in some of the conditions, as older adults, similar to younger ones, did not spontaneously bind information in working memory when there was no expectation to utilize the bound representation.…”
Section: Theoriesmentioning
confidence: 99%
“…On the other hand, three other articles that looked at hyperbinding provide mixed and somewhat qualified support for it. First, the article by McCormick-Huhn, Chen, Wyble, and Dennis (2018) looked at binding in working memory using attribute amnesia to test the limits of both the hyperbinding suggestions and those of the ADH. Their results did not support the hyperbinding position at least in some of the conditions, as older adults, similar to younger ones, did not spontaneously bind information in working memory when there was no expectation to utilize the bound representation.…”
Section: Theoriesmentioning
confidence: 99%
“…However, by this account, participants would be keeping more in mind as opposed to experiencing attentional narrowing associated with motivation. While it is conceivable that a higher working memory load during the motivated 1-back could lead to more fragile bound representations of face-name pairs in older adults (McCormick-Huhn et al, 2017), the point values were consistent throughout blocks and did not vary trial-by-trial. Therefore, it was unlikely that participants held this information in working memory as they knew what to expect consistently throughout a given block.…”
Section: Dass-21mentioning
confidence: 80%
“…Some evidence Manuscript to be reviewed showed that age selectively impaired cognitive control. Recent studies reported that old adults had selective difficulty in memorizing content-context associations but not in isolated contents (Artuso, Cavallini, Bottiroli, & Palladino, 2017;Artuso & Palladino, 2011;McCormick-Huhn, Chen, Wyble, & Dennis, 2018;Old & Naveh-Benjamin, 2008;Pelegrina, Borella, Carretti, & Lechuga, 2012) and the delays in selection were longer with a function of memory load (Artuso et al, 2017), implying that proactive control was impaired with aging. But Xiang et al (2016) reported that older adults had selective deficits in reactive control.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%